Biomethane Yield from Different European Phragmites australis Genotypes, Compared with Other Herbaceous Wetland Species Grown at Different Fertilization Regimes - Franziska Eller; Per Magnus Ehde; Claudia Oehmke; Linjing Ren; Hans Brix; Brian K. Sorrell; Stefan E. B. Weisner (Resources, 2020)
Phragmites australis, Typha latifolia, T. angustifolia and Arundo donax are tall wetland graminoids with the potential to replace fossil fuels under sustainable cultivation conditions. We investigated the biomethane (CH4) production of these four species, including four different genotypes of P. australis, which represent the high intraspecific diversity of European reed. All plants were grown under three different macronutrient supplies (no nutrients added, an equivalent of 75 kg N ha−1 year−1 added and an equivalent of 500 kg N ha−1 year−1 added). Biomethane production was measured in four independent batch digestion tests. Across all experiments, fertilization regime had little effect on CH4 yield, which was on average 222 ± 31 L kg−1 volatile solids (VS). The lowest yield was produced by T. angustifolia (140 L kgVS−1) receiving no nutrients, while the highest yield was produced by A. donax (305 L kgVS−1) in the highest nutrient treatment. The intraspecific diversity of P. australis did not affect biomethane production. All P. australis genotypes produced on average 226 ± 19 L CH4 kgVS−1, which, although high, was still lower than conventional biogas species. The biomass production of P. australis was less increased by fertilization than that of Typha sp. and A. donax, but all species had similar biomass without fertilization.